Knowledge of Noncommunicable Diseases and Social Media among Secondary School Teachers in Akinyele Local Government Area Oyo State Nigeria - Rukayat Ayanlola Sanni-Adeniyi; Musibau Titiloye; Ademola Ajuwon (Wolters Kluwer Medknow Publications, 2024)
Background: Social media (SM) are now widely available and can potentially play an important role in the prevention of noncommunicable diseases (NCDs). The school environment is a key location for educating children about NCDs and the teachers' level of knowledge may have an impact on them. This study investigated the knowledge of NCDs and SM among secondary school teachers. Materials and Methods: Using a self-administered questionnaire, data were collected from 423 randomly selected male and female secondary school teachers teaching in both public and private secondary schools located in Akinyele Local Government Area, Oyo State, in May 2018. Knowledge of SM was measured on a 10-point scale (scores 0-3, 4-6, and 7-10 were rated as poor, fair, and good, respectively), while knowledge of NCDs was measured on a 28-point scale (scores 0-8, 9-18, and 19-28 were rated as poor, fair, and good, respectively). Data were analyzed using descriptive statistics and multiple regression tests at a 5% level of significance. Results: Findings showed that the mean age of respondents was 33.5 ± 0.5 and 52.5% were female. About half (51.5%) of the respondents had good knowledge of SM. Less than half (28.1%) had good knowledge of NCDs. Knowledge of SM was significantly associated with age (P < 0.001), while knowledge of NCDs had no significant association. Conclusion: Based on these results, a gap exists regarding teachers' knowledge of NCDs. Health professionals may contribute to teacher training curriculum development to include health education targeted toward NCD prevention.